Perfectionistic environments and irrational beliefs on the transition to elite athletic performance: A longitudinal study - Ramis, Y.; Pons, J.; Alcaraz, S.; Pallares, S.; Viladrich, C.; Muñoz-Justicia, J.; Torregrossa, M. (International Journal of Environmental Research and Public Health, 2024)
This study aimed to longitudinally evaluate talented athletes` levels of perfectionism, irrational beliefs, and motivations with regard to their athletic careers. A total of 390 athletes from U14, U16, and junior categories (MageT1 = 15.42) answered shortened versions of the Sport-MPS2, iPBI, and BRSQ during two consecutive seasons, along with questions referring to their current and predicted prioritization of sports and education. Participants reported high levels of perfectionistic strivings and medium to low levels of socially prescribed perfectionism and concern over mistakes decreasing from T1 to T2. A decrease was also found for demandingness and awfulizing, but increased levels were found for depreciation in T2. Participants report very high intrinsic motivation with low levels of external regulation and amotivation, but intrinsic motivation decreased from season to season. This general profile varied depending upon future expectancies toward dedication to sports and education. Those who foresaw a prioritized dedication to sports presented significantly higher levels of socially prescribed perfectionism, perfectionistic strivings, and intrinsic motivation, while those who considered that sports would not be prioritized in the following 5 years reported higher levels of demandingness, awfulizing, depreciation, and amotivation. Additionally, while current levels of motivation (T2) seemed to be predicted mainly by previous motivation levels (T1), significant predictive capacity was also detected for socially prescribed perfectionism positively predicting external regulations and amotivation, perfectionistic strivings negatively predicting amotivation, and depreciation negatively predicting intrinsic motivation and positively predicting both extrinsic regulation and amotivation. We discuss the potential perils of developing extremely demanding environments, as they could potentially result in poor motivational profiles of athletes in their talent development stage during the junior to senior transition.